Academic Leadership Behavior of School Directors Affecting Learning Management of Teachers in Schools under Supervision of Phra Nakorn Si Ayutthaya Primary Educational Service Area Office 1 - Glommano, Supaporn; Rupan, Pornthep (Mahachula Academic Journal, 2021)
The purposes of this study were: (1) academic leadership behavior of school directors, (2) learning management efficiency of teachers in schools, and (3) academic leadership behavior of directors that affects the learning management efficiency of teachers in schools. The samples were 244 directors and teachers in Phra Nakorn Si Ayutthaya Primary Educational Service Area Office 1 by using sample random sampling. The research instrument was a questionnaire with reliability of academic leadership behavior of school directors was 0.98 and the reliability of teachers’ learning management was 0.96. The statistics used to analyzedata were mean, deviation, Pearson’s correlation coefficient and simple multiple regression analysis. The results of the study were found that (1) the academic leadership behavior of school directors in Phra Nakorn Si Ayutthaya Primary Educational Service Area Office 1 overall was at the high level, the aspect with the highest average was promoting the academic climate, followed by the teachers’ teaching assessment and the aspect with the lowest average was making action plan. (2) Learning management of teachers in schools of Phra Nakorn Si Ayutthaya Primary Educational Service Area Office 1 Overall, the practice was at a high level, the highest average was curriculum analysis, followed by interaction with students and the lowest average was learning management techniques. (3) The academic leadership behavior of school directors ; consist of making action plan, curriculum administration, promoting academic climate and teachers’ teaching assessment that affecing the learning management of the teachers in schools under supervision of Phra Nakorn Si Ayutthaya Primary Educational Service Area Office 1 of significance was statistically at the 05 level.